Adsorption and corrosion inhibition of mild steel in hydrochloric acid solution by S-allyl-O,O′-dialkyldithiophosphates - Chuan Lai; Bin Xie; Like Zou; Xingwen Zheng; Xiao Ma; Shasha Zhu (Results in Physics, 2017)
Here, S-allyl-O,O′-diphenyldithiophosphate(SOD1), S-allyl-O,O′-dibenzyldithiophosphate (SOD2) and S-allyl-O,O′-di(2-phenylethyl)dithiophosphate(SOD3) were successful synthesized and characterized, which acting as the novel corrosion inhibitors for mild steel in hydrochloric acid (HCl) solution were evaluated by electrochemical measurements, weight loss measurement and scanning electron microscopy. Potentiodynamic polarization measurement indicates that the synthesized inhibitors are effective mixed-type inhibitors. The inhibition efficiency increases with inhibitor concentration increasing, decreases with HCl concentration and temperature increasing. The adsorption of SOD1, SOD2 and SOD3 on mild steel surface obeys Langmuir isotherm. The adsorption of SOD1 and SOD3 on mild steel surface is a mixed adsorption involving both physisorption and chemisorption, and that the adsorption of SOD2 on mild steel surface belongs to chemical adsorption. Keywords: Corrosion inhibitor, Mild steel, Polarization, Weight loss, Adsorption